Parent-of-origin effects on seed development in Arabidopsis thaliana. - Scott, R; Spielman, M; Bailey, J; Dickinson, H (1998)
Many flowering plants are polyploid, but crosses between individuals of different ploidies produce seeds that develop abnormally and usually abort. Often, seeds from interploidy crosses develop differently depending on whether the mother or father contributes more chromosome sets, suggesting that maternal and paternal genomes are not functionally equivalent. Here we present the first cytological investigation of seed development following interploidy crosses in Arabidopsis thaliana. We find that crosses between diploid and tetraploid plants in either direction, resulting in double the normal dose of maternal or paternal genomes in the seed, produce viable seeds containing triploid embryos. However, development of the seed and in particular the endosperm is abnormal, with maternal and paternal genomic excess producing complementary phenotypes. A double dose of maternal genomes with respect to paternal contribution inhibits endosperm development and ultimately produces a smaller embryo. In contrast, a double dose of paternal genomes promotes growth of the endosperm and embryo. Reciprocal crosses between diploids and hexaploids, resulting in a triple dose of maternal or paternal genomes, produce seeds that begin development with similar but more extreme phenotypes than those with a double dose, but these invariably abort. One explanation of our observations is that seeds with maternal or paternal excess contain different doses of maternally or paternally expressed imprinted loci affecting endosperm development.